Antioxidant and cytotoxic activity of new di- and polyamine caffeine analogues. (3rd June 2018) - Jasiewicz, Beata; Sierakowska, Arleta; Jankowski, Wojciech; Hoffmann, Marcin; Piorońska, Weronika; Górnicka, Agnieszka; Bielawska, Anna; Bielawski, Krzysztof; Mrówczyńska, Lucyna
Abstract: A series of new di- and polyamine-caffeine analogues were synthesised and characterised by NMR, FT-IR, and MS spectroscopic methods. To access the stability of the investigated caffeine analogues, molecular dynamic simulations were performed in NAMD 2.9 assuming CHARMM36 force field. To evaluate the antioxidant capacity of new compounds, three different antioxidant assays were used, namely 1, 1-diphenyl-2-picryl-hydrazyl free radical (DPPH ) scavenging activity, ferrous ions (Fe 2+ ) chelating activity, and Fe 3+ →Fe 2+ reducing ability. In vitro, the ability of new derivatives to protect human erythrocytes against oxidative haemolysis induced by free radical from 2, 2′-azobis(2-methylpropionamidine) dihydrochloride (AAPH) was estimated. The cytotoxic activity was tested using MCF-7 breast cancer cells and human erythrocytes. All compounds showed the antioxidant capacity depending mostly on their ferrous ions chelating activity. In the presence of AAPH, some derivatives were able to effectively inhibit the oxidative haemolysis. Two derivatives, namely 8-(methyl(2-(methylamino)ethyl)-amino)caffeine and 8-(methyl(3-(methylamino)propyl)amino)caffeine, showed cytotoxic activity against MCF-7 breast cancer cells but not against human erythrocytes. Therefore, it is concluded that the selected di- and polyamine caffeine analogues, depending on their chemical structure, were able to minimise the oxidative stress and to inhibit the tumour cell growth. The confirmed antioxidant and cytotoxic properties of some caffeine derivatives make them attractive for potential applications in food or pharmaceutical industries.